2.4k views
3 votes
4h + 9 = 3 + (-h + 46)

User Redithion
by
6.5k points

2 Answers

5 votes
  • u should start of with simplifying the equation
4h + 9 = 3 + (-h + 46)-example-1
User Arquelio
by
6.0k points
7 votes

Answer:
h=8

Explanation:

To find the value of "h" you need to:

Remember the multiplication of signs:


(+)(+)=+\\(-)(-)=+\\(-)(+)=-

Distribute the positive sign that is outside the parentheses to eliminate the parentheses:


4h + 9 = 3 -h + 46

Add like terms on the righ side of the equation:


4h + 9 = -h + 49

Add h to both sides:


4h + 9+h = -h + 49+h


5h + 9 =49

Subtract 9 from both sides:


5h + 9-9=49-9


5h =40

Divide both sides by 5:


(5h)/(5)=(40)/(5)\\\\h=8

User Taranfx
by
5.2k points